(3TQM GdedNU aj GdgjFIs - (3UdGM GdOjf ehSi Hf eMeO Hf (B( (3GdbGVi (B) (3eMehO GdQhei GdeYQha HbGVi RGOI ehSi LdHis; (3eMehO Hf eMeO Hf YeQ GdLZejfj GdNhGQRej,J (B744 (3g` s ((3eMi GdOjf Hf HOQ GdOjf GdCHGQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdTeS VjGA hHYO JdbJ GdeNJUQ GdeSei HGdedNU ai GdgjFI Gfi CdaJ gPG GdcJGH ai HjGf gjFI HSGW CLSGe GdYGde s
(3BNQgG (B:s
(3hYTQI CjGe hEMOi hYTQhf SGYI EdG ObjbI hKdGKI CNeGS ObjbI ef ObGFb GdSGYGJ hgh CHQY GdMSGHjf gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG CTcGds
(3aQZ efg GdTGQM SfI (B815 (3Ch SfI (B820 (3hbOeg dCdZ Hc ejQRG HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs